The Mystery of the Lorentz Transform: A Reconstruction and Its Implications for Einstein’s Theories of Relativity and cosmology. (JOURNAL OF ADVANCES IN PHYSICS, 2021)
The Lorentz Transformation (LT) is an arbitrary and poorly conceived mathematical tool designed to make Maxwell’s electromagnetism conform to Galilean relativity, which formed the basis of classical mechanics and physics. A strange combination of this transform with an axiomatic assumption by Albert Einstein that the velocity of light c is an absolute and universal constant has led to an idealist, geometrical and phenomenological view of the universe, that is at variance with objective reality. This conundrum that has lasted for more than hundred years has led to rampant mysticism and has impaired the development of positive knowledge of the universe. The present reconstruction of LT shows that the gamma term, which fueled mysticism in physics and cosmology is, on the contrary, a natural outcome of the subjective geometrical rendition of the speed of light and the idealist unification of abstract space and time into a 4D “spacetime” manifold; by Minkowski and Einstein. Only a materialist dialectical perspective of space and time can rid physics of all mysticism arising out of LT; from the quantum to the cosmic.